Investigation of Flood Characteristics Due to Dam Failure in the Narrow Section of the Rive - Azad Miraki; Jamil Bahrami; Ata Amini (محیط زیست و مهندسی آب, 2020)
In this study, changes in flood characteristics due to the failure of Vahdat Dam (Gheshlagh) in areas where the cross section of the river has changed, because of human activities, were investigated. For this purpose, the HEC-RAS model was used to simulate the failure of the dam and the resulting flood flow. Data on the dam structures and flow of the Gheshlagh River in Kurdistan Province, on which the Vahdat Dam is located, were obtained from the Kurdistan Regional Water Company. Using the ArcMap software, after converting the digital elevation model (DEM) to a three-dimensional model (TIN), the required parameters and lines related to the cross sections on the river were drawn. This data was transferred to the HEC-RAS model. Through field studies, cross sections were corrected and Manning coefficient was measured in different zones. After preparing images of bridges and embankments along the flow path, the height of the bridge and the embankments in the flow path were measured using station GPS. The Grize Bridge and the location of the studied embankments in this study located 23 and 33 km downstream of the Vahdat Dam, respectively, were selected to investigate the changes in flood characteristics due to local narrowing. Changes in water height and width in the study areas were investigated. At the site of the Grize Bridge, the peak of flooding due to dam failure and water depth was 4773.79 m3/s and 10 m, respectively. These values ​​at the embankments were 4330.04 m3/s and 10.8 m, respectively. Comparing these numbers with the data calculated in the previous sections of these contracted sites indicates a significant reduction in the flow capacity.